An examination of recent research of water absorption behavior of natural fiber reinforced polylactic acid (PLA) composites: A review - Azka, Muhammad Adlan; Sapuan, S.M.; Abral, Hairul; Zainudin, E.S.; Abdul Aziz, Faieza (Elsevier, 2024)
Researchers have begun focusing on developing biodegradable materials, such as natural fiber/polymer composites (NFPC), since the growing of environmental concerns related to waste management. One crucial aspect that must be established in the development of these composites is their water-absorption behavior. This paper examines the water absorption (WA) behavior of NFPC, with a specific emphasis on natural fiber/polylactic acid (PLA) composites. It discusses processes and numerous aspects related to this behavior, based on recent published research. This review analyzes the influence of several factors, such as the loading of natural fiber, the combination of different natural fibers, the methods used in manufacturing, and the temperature of the water, on the WA behavior of natural fiber/PLA composites. It also explores how WA affects the properties of these composites. In addition, this review also presented techniques for improving the WA resistance of the composites. This review paper provides researchers with insights into the WA behavior of the composites, aiming to facilitate the development of a versatile and eco-friendly material that may effectively address waste disposal challenges.